Ultra-morphological studies on enamel-universal adhesive interface. (January 2021) - Aung, San San May Phyo; Takagaki, Tomohiro; Ikeda, Masaomi; Tagami, Junji
Abstract: Objectives: Nowadays, the universal adhesives are often used for silane application prior to application of self-adhesive resin cements. The purpose of this study was to evaluate enamel surface roughness and to observe the enamel-adhesive interface after acid-base challenge using three different self-adhesive resin cements combined with universal adhesives. Materials and Methods: Three self-adhesive resin cements: PANAVIA SA Luting Cement Plus (SA), Calibra Universal (CA) and MaxCem Elite Chroma (MC) which in conjunction with the particular universal adhesives: Clearfil Universal Bond Quick (UQ), Prime&Bond Universal (PB) and Optibond Universal (OB) were tested. Thirty enamel surfaces from caries-free human premolars were ground and bonded with the tested self-adhesive resin cements combined with universal adhesives. The surface roughness test (Sa) with or without applying adhesives was performed with 3D-CLSM. The interface of the bonded specimens after acid-base challenge was also examined by SEM. Results: The Sa of OB was significantly higher than those of PB and UQ. There were statistically significant differences among all of the groups ( p < 0.05). An acid-base resistant zone (ABRZ) was observed in all groups, however, formation of the ABRZ was material dependent. Conclusion: OB provided most etching performance to enamel of human premolars and MC group with OB presented durability against acid-base challenge. Clinical significance: Nowadays, the combination of self-adhesive resin cement and universal adhesive may be a viable option for a reliable bonding performance and bonding durability in indirect restorative dentistry.